Test the Potential of Macadamia Nut Oil (Macadamia F. Muell) As Sunscreen in Cream Preparations In Vitro - Yessy Ulandari Natasia; Sri Wahyuni Nasution; Tri Suci (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background: Sunlight has a beneficial effect by activating provitamin D3 found in the epidermis of the skin to become vitamin D3. However, excessive sun exposure can also have detrimental effects, especially on the skin. Macadamia nut oil contains vitamin E (tocotrienols and tocopherols) which are natural antioxidants. Macadamia nut oil also contains linoleic acid which is great for softening the skin, regenerating skin cells, moisturizing the skin, and is a natural anti-inflammatory. and helps restore skin barrier function and reduce transepidermal water loss (TEWL). Objectives: To determine whether there is a sunscreen potential from macadamia nut oil, the difference in the SPF value is significant between cream preparations with the addition of macadamia nut oil in various concentrations and to determine the sunscreen category of each macadamia nut oil formulation. Methods: This research was carried out experimentally, including the preparation of macadamia nut oil lotion, pH test, irritation test, and in vitro determination of the SPF (sun protection factor) number using a UV-Vis spectrophotometer. Results: The addition of macadamia nut oil combined with oxybenzone and octylmetoxycinamate in cream preparations has an average SPF value of F1 (blank) of 9.97; F2 (blank + 2% oxybenzone + 5% octyl methoxycinamate) of 23.14; F3 (1% macadamia nut oil) of 29.39; F4 (5% macadamia nut oil) of 32.99; and F5 (10% macadamia nut oil) of 37.59. The addition of macadamia nut oil in various concentrations gave a significant difference in increasing the SPF value between each formula combined with oxybenzone and octylmetoxycinamate. Conclusion: The addition of macadamia nut oil can increase the effectiveness of the combination oxybenzone and octylmetoxycinamate sunscreen in cream preparations.